PENGARUH IAA DAN GA3 TERHADAP PERTUMBUHAN VEGETATIF BIBIT ANGGREK DENDROBIUM Walter Ouemae 4N x Singapore White - , Krisantini; Meijliani Tanu; , Irawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1999)
The objective of the experiment was to study the effect of lAA and GA3 on vegetative growth of Dendrobium orchids. The experiment was carried out using 10 months-old orchid plants, and consists of two treatments, one with lAA of 0, 30, 60, and 90 ppm and the other with GA3 of and 100 ppm. The experiment was conducted at Baranang Siang Research Centre of Bogor: Agriculture University. Each treatment was replicated three times. Data were taken on number of leave, height, leaf size, number of roots, and number of pseudobulbs. Application of IAA up to 90 ppm increased the number of leaves, leaf size, height, number of roots and number of pseudobulbs. Application of 100 ppm GA 3 increased number of leaves and number of roots. Application of 90 ppm IAA combined with 100 ppm GA3 significantly increased number of roots and leaf size of orchid plants.